2009
DOI: 10.1002/anie.200902148
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Hydroxylation of Aryl Halides under Ambient Conditions

Abstract: In this Communication entry 16 in Table 3 shows the wrong substrate and the wrong product: 4-bromoacetophenone as the substrate and 4-hydroxyacetophenone as the product should be replaced by 4-bromobenzophenone and 4-hydroxybenzophenone, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(55 citation statements)
references
References 25 publications
2
53
0
Order By: Relevance
“…[a] Reagents and conditions: [a] ArCl/NH 3 /NaOtBu = 1:3-4:2, chlorobenzene at room temperature resulted in the quantitative formation (as evident by 31 P NMR spectroscopy) of a new species after 3 hours (Figure 1). Solution NMR spectroscopy and X-ray crystallographic studies confirmed the identity of this species as being the square planar Pd II complex C1, in which L7 is coordinated in a k 2 -P,N fashion with Cl trans to P. [19][20][21] Complex C1 was also prepared successfully from alternative Pd sources in excellent yield ([CpPd(allyl)], 93 %; [(cod)Pd(CH 2 TMS) 2 ], 99 %). The analogous 4-anisolyl derivative C2 was prepared in a similar manner and displays solution and solid state characteristics analogous to C1.…”
mentioning
confidence: 90%
“…[a] Reagents and conditions: [a] ArCl/NH 3 /NaOtBu = 1:3-4:2, chlorobenzene at room temperature resulted in the quantitative formation (as evident by 31 P NMR spectroscopy) of a new species after 3 hours (Figure 1). Solution NMR spectroscopy and X-ray crystallographic studies confirmed the identity of this species as being the square planar Pd II complex C1, in which L7 is coordinated in a k 2 -P,N fashion with Cl trans to P. [19][20][21] Complex C1 was also prepared successfully from alternative Pd sources in excellent yield ([CpPd(allyl)], 93 %; [(cod)Pd(CH 2 TMS) 2 ], 99 %). The analogous 4-anisolyl derivative C2 was prepared in a similar manner and displays solution and solid state characteristics analogous to C1.…”
mentioning
confidence: 90%
“…[8] Considering the ready availability and low toxicity of copper catalysts and their ligands, [9] the development of a cheaper copper-catalyzed system enabling the direct hydroxylation of aryl halides has become an important goal. Very recently, the efficient copper-catalyzed synthesis of phenols from aryl halides was reported under milder conditions (100-130 8C), and research showed that a well-defined ratio of water/organic solvent was the key factor for the success of the method, however, water alone was inefficient.…”
mentioning
confidence: 99%
“…Given the ubiquity of heterocyclic motifs in medicinal, biological, and naturalp roducts chemistry,w es ought to evaluate the compatibility of electrophilic coupling partners featuring such functionality in the mono-a-arylation of acetone at room temperature using the [Pd(cinnamyl)Cl] 2 /CyPF-tBu catalyst system (Figure 4). It is worthy of mention that while selected transformations of heterocycle-containing substrates have been featured in past reports on palladium-catalyzed acetone mono-a-arylation conducted at elevated temperature, [14,[16][17][18] such couplingp artnersh ave for the most part been overlooked in this chemistry.I nt his context we were pleasedt o observe that substituted pyrrole (17), pyridine (18,19), isoquinoline (20), quinoline (21,22), quinaldine (23), (benzo)thiophene (24,25), benzothiazole (26), and benzodioxole (27)c oupling partners functioned welli no ur newly developed room temperature acetone mono-a-arylation chemistry (Figure 4,.…”
Section: àCspmentioning
confidence: 98%
“…As such, the identification of alternative catalysts that are capable of promoting such transformations at room temperature would represent an important advance. Indeed, it is worthy of mention that while progress has been made with regardt ot he development of myriad palladium-catalyzed room temperature transformations using relatively inexpensive and abundant (hetero)aryl chloride reaction partners, [15,20] relatede xamples of room temperature ketone mono-a-arylation chemistry are limited to four table entries involving( IPr)Pd-catalyzed transformationso fp ropriophenone (41-75 %). [21] Herein, we report the first examples of acetone mono-a-arylation chemistry conducted at room temperature, which is achieved through use of ap alladium catalysts ystem featuring the JosiPhos [22] ligand variant CyPF-tBu depicted in Figure 1.…”
Section: àCspmentioning
confidence: 99%